Ultraviolet ray wavelength in Gafchromic XR-RV3 and XR-SP2 films. (September 2016) - Kuwano, T.; Takeda, Y.; Katsuda, T.; Gotanda, R.; Gotanda, T.; Akagawa, T.; Tanki, N.; Noguchi, A.; Yabunaka, K.
Abstract : Introduction: Gafchromic films have been used for the measurement of X-ray dose in diagnostic radiology. Correlation between color density change and ultraviolet (UV) wavelength of Gafchromic XR-RV3 and XR-SP2 were studied. UV irradiation is considered as an X-ray substitute in the double exposure technique. It is one of the correction methods for the nonuniformity error of Gafchromic XR-RV3 and XR-SP2. Purpose: It is to determine the UV suitable wavelength of a UV light emitting diode (UV LED) that is used as a substitute for X-rays in the double exposure technique for the Gafchromic XR-RV3 and XR-SP2. Materials and methods: UV LED that UV rays at a wavelength of 353 nm and 5-nm increments from 360 to 400 nm were used. Gafchromic XR-RV3 or XR-SP2 was irradiated with UV of different wavelengths through the 30 mm diameter of irradiation hole for 2 and 4 h, at a distance of 53 mm, respectively. Gafchromic XR-RV3 or XR-SP2 was fixed onto an acrylic plate of 3 mm thickness for assistance with scan. A circular region of interest (ROI) of 0.5 inch for measurements of pixel value was set in the center of the UV irradiation region. The mean pixel values ± standard deviation (SD) was obtained. Results: Indicated high pixel value of Gafchromic XR-RV3 and XR-SP2 were 1276.81 ± 254.30 (395 nm) and 576.46 ± 219.75 (400 nm), respectively. Conclusions: The irradiation of Gafchromic XR-RV3 and XR-SP2 with homogeneous UV rays by the UV-LED wavelengths of 395 or 400 nm can correct the nonuniformity error of the active layer efficiently. Disclosure: Research supported byJSPS KAKENHI Grant Number26460740 .